Proposal for a pacemaker implant technique with minimum radiation exposure - Cray da Costa, Mário Augusto; Grczczak, Robson Cesar Vaz; Machado, Lucas Vinícius Mamadi; de Souza, Ana Carolina Mello Fontoura (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Objective: To describe a standardized technique for implanting a pacemaker to reduce the time of surgery and radiation exposure and to demonstrate the results in a series of patients. Methods: Through descriptive and cross-sectional statistics, 109 patients undergoing dual-chamber (DDD) and single-chamber (VVI) pacemaker implantation were evaluated, using a standardized technical approach used in the cardiac surgery service of Santa Casa de Misericórdia of Ponta Grossa-PR, Brazil, from November 2016 to November 2019. Clinical aspects, implant indication, implant times, and radiation time were studied. The technique was described, and its most relevant aspects were discussed. Results: 68.81% of the pacemakers were DDD and the surgical time ranged from 11’22’’ to 34’43’’, with a median of 18’15’’. In these cases, the fluoroscopy time ranged from 34’’ to 5’10’’, with a mean of 1’42’’ and a 16.9 mGy median amount of radiation. The time to implant the VVI pacemaker ranged from 12’ to 42’, with a median of 17’12’’. The fluoroscopy time ranged from 26’’ to 6’25’’, with a mean of 1’41’’ and the median amount of radiation was 13.6 mGy. Conclusion: The technique proved to be agile, safe, with low fluoroscopy times and small amount of radiation. There were no postoperative complications. However, few studies were found for comparison.